2016
DOI: 10.1038/onc.2016.425
|View full text |Cite
|
Sign up to set email alerts
|

SIRT4 inhibits malignancy progression of NSCLCs, through mitochondrial dynamics mediated by the ERK-Drp1 pathway

Abstract: SIRT4 is well-known for its deacetylase activity in energy metabolism, but little is known about its roles in carcinogenesis. We demonstrated that SIRT4 was decreased in 70 out of 133 non-small cell lung cancer (NSCLC) cases by immunohistochemical staining and localized in the mitochondria using confocal microscopy. Low levels of SIRT4 expression was correlated with tumor node metastasis (TNM) stage, histological type of tumor (adenocarcinoma), lymph nodal status, Ki-67 (proliferation index) and poor overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 38 publications
10
90
0
Order By: Relevance
“…SIRT4 is located primarily in the mitochondrial matrix and involved in a variety of events in mitotic cells (Fu et al., 2016). Differential roles of SIRT4 have been reported in diverse cell types and multiple tissues.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT4 is located primarily in the mitochondrial matrix and involved in a variety of events in mitotic cells (Fu et al., 2016). Differential roles of SIRT4 have been reported in diverse cell types and multiple tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt4 mRNA levels are reduced in many human cancers, such as lung, pancreatic, ovarian, gastric, colorectal, prostate, renal, liver, and endometrial cancer as well as hematological tumors (33-45) ( Table 1). Lower levels of Sirt4 protein expression in tumor tissues are often associated with worse pathological grading and reduced survival in cancer patients, and Sirt4 KO mice display an increased incidence of spontaneous tumors (2,33,36,37,44,45,49).…”
Section: Sirt4 As a Context-dependent Tumor Suppressor And Oncoproteinmentioning
confidence: 99%
“…Recent studies on SIRT4 suggest that it drives mitochondrial fusion through negative regulation of fission proteins and positive regulation of fusion proteins. SIRT4 overexpression in lung cancer‐derived cell lines results in more fused mitochondria and reduced mitochondrial fission via downregulation of DRP1 expression and inhibition of Ser 616 phosphorylation . Further evidence for SIRT4 regulation of mitochondrial dynamics comes from another in vitro study in cell lines in which SIRT4 overexpression was observed to drive mitochondrial fusion and was associated with an enrichment of L‐OPA1, the fusion‐promoting long form of OPA1, relative to S‐OPA1 .…”
Section: Introductionmentioning
confidence: 99%